“I was born and raised in Indonesia. Should I own English?” Exploring Indonesian students’ preferences and ownership of English - Gandana, Isti Siti Saleha; Anjani, Nissa; Imperiani, Ernie (Universitas Ahmad Dahlan, 2025)
The mushrooming of English varieties across the globe has been one of the consequences of the status of English as an international language, making it a pluricentric language. Despite the global attention towards English, little is known about how Indonesian learners relate personal preference to language ownership. Drawing on Kachru’s (1992) three concentric circles and Widdowson’s (1994) language ownership, this study explores a total of thirty-four final-year Indonesian university students’ preferences and sense of ownership towards English. Through a qualitative case study research design, in which a questionnaire and interviews were employed to collect data, the study pointed to American English to be the most preferred, and by far the most popular, English variety among the students, followed by British and Australian English. While the students’ preference was tightly connected to the kind of English they were mostly exposed to as they were learning the language, the findings confirm that the inner circle varieties still hold more currency in comparison to other varieties. Yet, despite the more than decade-long of knowing, learning and engaging with the language, most of the students felt ambivalent in regard to their sense of ownership toward English. They indicated that language ownership transcends the ability to speak the language; rather, it is intricately intertwined with one’s sense of identity. This study calls for a more concerted effort to familiarize students with the different varieties of English in the classroom, hence making them more aware of the ideological dimension—such as native-speakerism—attached to the language.